Nitrate and Nitrite Treatment Modulate Performance and Available Fuel Sources In Zebrafish Muscle and Liver. (29th May 2020) - Keller, Rosa; Beaver, Laura; Reardon, Patrick; Hord, Norman
Abstract: Objectives: Treatment with nitrate, but not nitrite, improves exercise performance but the mechanisms responsible are not fully understood. Thus, we tested the hypothesis that nitrate and nitrite treatment alter exercise performance through regulation of genes related to glucose and lipid metabolism in skeletal muscle and liver. Furthermore, we tested the hypothesis that nitrate treatment caused increased abundance and utilization of metabolic fuels in muscle that require less oxygen for energy production. Methods: Adult zebrafish fish were exposed to sodium nitrate (606.9 mg NaNO3 /L water), sodium nitrite (19.5 mg NaNO2 /L of water), or control water for 21 days (n = 9–12/treatment). Liver and muscle gene expression were analyzed by quantitative real-time PCR and liver and muscle metabolomes were assessed by 1 H-NMR untargeted metabolomics. Results: Nitrite treatment significantly increased carnitine palmitoyl transferase 1b ( cpt1b) expression in the liver and significantly decreased acetyl-CoA carboxylase ( acaca) expression in skeletal muscle. Nitrate treatment significantly increased expression of peroxisome proliferator activated receptor-γ ( pparg) muscle while acaca significantly decreased in skeletal muscle. Nitrate treatment also induced significant increases in metabolic fuels, such as ATP and creatine phosphate, and fuel sources including β-hydroxybutyrate and glycolytic intermediates in rested skeletal muscle. After a graded exercise test, these metabolites decreased in skeletal muscle of nitrate-treated fish while they increased with exercise in the skeletal muscle of control-treated zebrafish. Conclusions: Our data are consistent with the hypothesis that nitrate treatment altered lipid and carbohydrate metabolism of zebrafish, in part, through a pparg mediated mechanism in the liver, and may improve exercise performance through utilization of fuel sources that require less oxygen during exercise. In contrast, our data indicate that nitrite may attenuate exercise performance, in part, by promoting dependence on fatty acid oxidation in the liver of zebrafish. These mechanisms may mediate improved exercise tolerance in populations with cardiovascular disease. Funding Sources: Celia Strickland and G. Kenneth Austin III Endowment and National Institutes of Health.